Hypoacylated LPS from Foodborne Pathogen Campylobacter jejuni Induces Moderate TLR4-Mediated Inflammatory Response in Murine Macrophages - Korneev, Kirill V.; Kondakova, Anna N.; Sviriaeva, Ekaterina N.; Mitkin, Nikita A.; Palmigiano, Angelo; Kruglov, Andrey A.; Telegin, Georgy B.; Drutskaya, Marina S.; Sturiale, Luisa; Garozzo, Domenico; Nedospasov, Sergei A.; Knirel, Yuriy A.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Toll-like receptor 4 (TLR4) initiates immune response against Gram-negative bacteria upon specific recognition of lipid A moiety of lipopolysaccharide (LPS), the major component of their cell wall. Some natural differences between LPS variants in their ability to interact with TLR4 may lead to either insufficient activation that may not prevent bacterial growth, or excessive activation which may lead to septic shock. In this study we evaluated the biological activity of LPS isolated from pathogenic strain of Campylobacter jejuni, the most widespread bacterial cause of foodborne diarrhea in humans. With the help of hydrophobic chromatography and MALDI-TOF mass spectrometry we showed that LPS from a C. jejuni strain O2A consists of both hexaacyl and tetraacyl forms. Since such hypoacylation can result in a reduced immune response in humans, we assessed the activity of LPS from C. jejuni in mouse macrophages by measuring its capacity to activate TLR4-mediated proinflammatory cytokine and chemokine production, as well as NFκB-dependent reporter gene transcription. Our data support the hypothesis that LPS acylation correlates with its bioactivity.